Implementing Social Media in Public Relations Tourism: SWOT Analysis - Pradini, Gagih; Awaloedin, Dipa Teruna; Ananda, Tiara Martha; Andini, Davi Ayu (CV ODIS, 2024)
The tourism sector in Indonesia, overseen by the Ministry of Tourism and Creative Economy, is undergoing continuous enhancement, leveraging the country's competitive advantages in the global tourism landscape. Government initiatives, strategically developed under the comprehensive framework highlighted by Hermawan (2019), focus on strengthening Destination, Marketing, and Human Resources. In the digital age, Social Media emerges as a transformative force, serving as a versatile platform to disseminate information, cultivate a positive image, and establish meaningful relationships. This study delves into the multifaceted strategies of implementing Social Media in Tourism Public Relations (PR), exploring models like POP and POSE. While the benefits include heightened visibility and credibility, challenges arise from intense competition and the need for effective utilization. Addressing these challenges requires a strategic approach, including SWOT analysis and collaborative efforts with various stakeholders. The study identifies key problems, aiming to understand the impact of social media on communication effectiveness and tourist destination image. The qualitative research methodology, supported by a literature review, examines the factors influencing the success or failure of social media implementation, utilizing SWOT analysis as a tool for strategic evaluation.